2014
DOI: 10.1103/physreva.89.062102
|View full text |Cite
|
Sign up to set email alerts
|

PTsymmetry in the non-Hermitian Su-Schrieffer-Heeger model with complex boundary potentials

Abstract: We study the parity-and time-reversal (PT ) symmetric non-Hermitian Su-Schrieffer-Heeger (SSH) model with two conjugated imaginary potentials ±iγ at two end sites. The SSH model is known as one of the simplest two-band topological models which has topologically trivial and nontrivial phases. We find that the non-Hermitian terms can lead to different effects on the properties of the eigenvalues spectrum in topologically trivial and nontrivial phases. In the topologically trivial phase, the system undergos an ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(138 citation statements)
references
References 52 publications
4
134
0
Order By: Relevance
“…Regarding model-building schemes for finite quasi-hermitian Hamiltonians, different techniques may be employed to yield different useful results. The correspondence between useful models of solid state physics and lattice quasi-hermitian operators has proven fruitful very recently [15,16]. Also, the correspondence between (non-normalized) orthogonal polynomials [34] and quantum-mechanical matrix models in has produces some interesting output [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding model-building schemes for finite quasi-hermitian Hamiltonians, different techniques may be employed to yield different useful results. The correspondence between useful models of solid state physics and lattice quasi-hermitian operators has proven fruitful very recently [15,16]. Also, the correspondence between (non-normalized) orthogonal polynomials [34] and quantum-mechanical matrix models in has produces some interesting output [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…5, which surpasses the previously examined toy models (e.g. [15]) both in sparsity and simplicity of the resulting pseudometric matrix elements.…”
Section: The Special Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Does there exist a topologically nontrivial system described by non-Hermitian Hamiltonian? This problem was considered by some authors [16,17,18,19,20,21]. Hu and Hughes [16] and Esaki et al [17] studied non-Hermitian generalization of topologically insulating phase at almost the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Schomerus considered a one dimensional nonHermitian tight binding lattice with staggered tunneling amplitude and showed that the system admits complex spectrum [19]. Another attempt has recently been made to find non-Hermitian Hamiltonian admitting topological insulator phase [20]. Zhu, Lu and Chen specifically considered non-Hermitian Su-Schrieffer-Heeger model with two conjugated imaginary potential located at the edges of the system [20].…”
Section: Introductionmentioning
confidence: 99%